ANTIPLATELET ACTIVITY OF PAPAYA LEAF EXTRACT (Carica papaya L) IN MICE - Rosida hari (AKADEMI FARMASI JEMBER, 2023)
Papaya leaves have a number of alkaloid compounds (carpaine, pseudocarpaine, dehydrocarpaine I, dehydrocapaine II and emetine. Carpaine is piperidin alkaloid. The piperidin alkaloid have activity of antiplatelet. This study aims to determine the antiplatelet activity of papaya leaf extract againts male mice. Desain of this research is pure experimental research with pre test – post test control group design. Subjects consisted of 4 groups of mice each group consisted of 5 mice. This study was devided into 4 groups : negative control CMC Na 1%, papaya leaf extract (Carica papaya L) concentration 10%/30g BB, papaya leaf extract (Carica papaya L) 25%/30g BB and papaya leaf extract (Carica papaya L) 50%/30g BB. Method of determined antiplatelet based on parameters using the tail bleeding time. Then the time bleeding was determind on day 0 and day 7. After the percentage increase of bleeding time stastical data were analyzed by one way analysis of variance (ANOVA). The results showed that the yield of papaya leaf extract was 17.6% with 96% ethanol solvent.Research result was found bleeding time with percentage of successive increase in extract papaya leaf 10% (84,33),extract papaya leaf 25% (157,70) and papaya leaf extract 50% (177,53). The result of data analysis using one way anova showed the difference between bleeding time and the value (sig F=0,000). This result showed a significant difference between treatment groups.